Monochromatic cycle partitions in random graphs - Lang, Richard; Lo, Allan (Combinatorics, probability & computing, 2021)
Erdős, Gyárfás and Pyber showed that every r-edge-coloured complete graph Kn can be covered by 25 r2 log r vertex-disjoint monochromatic cycles (independent of n). Here we extend their result to the setting of binomial random graphs. That is, we show that if - - - - - , then with high probability any r-edge-coloured G(n, p) can be covered by at most 1000r4 log r vertex-disjoint monochromatic cycles. This answers a question of Korándi, Mousset, Nenadov, Škorić and Sudakov.
First published online 14 August 2020
Gesehen am 09.09.2021